Caridina vithuraensis sp. nov. (Decapoda: Atyidae) from Vamanapuram River, Kerala region of Western Ghats, India - Vijayamma, Jayachandran Kunjuraman; Thomas, Tessa (Zootaxa, 2012)
A new species of Caridina H. M. Edwards, 1837, namely, C. vithuraensis, collected from Kallar, a tributary of Va-manapuram River, Kerala at Vithura is being described in this paper. The species is characterized by : small shrimps hav-ing short rostrum, extending to the tip of 1st segment of antennular peduncle, rarely reaching beyond, rostral formula : 11–19/2–5 (2–5 post-orbital); carpus of 1st pereiopod deeply excavated, 1.3 to 1.45 times as long as broad; dactylus of 3rdpereiopod ends in a terminal spine and with 5–7 accessory spines; dactylus of 5th pereiopod with 24–45 comb-likespinules; appendix interna on endopod of male 1st pleopod is prominent; uropodal diaeresis with 16–20 spines; telson con-ical in shape with 4–6 pairs of spinules on the dorsal and 6–8 spinules at the distal end. The species shows affinities withspecies like C. malayensis Cai et al., 2007; C. congoensis Richard & Clark, 2009 and C. roubaudi Richard & Clark, 2009. However they can be separated based on the specific characters given in Table 1.